Respuesta :

(x-6)(x+2)=0
x-6=0, x=6
x+2=0, x=-2
least -2, greatest 6

Hi :)

Ok, well- solve the equation first, then maybe from there we will have more ideas on what to do here.

So:

(x - 6)(x + 2) = 0

Set factors equal to 0

x - 6 = 0 or x + 2 = 0

x = 0 + 6 or x = 0 - 2

x = 6 or x = -2

Now we can answer the questions....

1) For (x - 6)(x + 2) to equal 0, either (x - 6) or (x + 2) must equal 0

2) In order from least to greatest, are -2 and 6


Let me know if you have any questions. As always, it is my pleasure to help students like you!